Analysis of Wear Behaviour of AA5052 Alloy Composites by Addition Alumina with Zirconium Dioxide Using the Taguchi-Grey Relational Method - Bhiksha Gugulothu; S. Lakshmi Sankar; S. Vijayakumar; Adina Srinivasa Vara Prasad; M. Thangaraj; M. Venkatachalapathy; T.V.Janardhana Rao (Advances in Materials Science and Engineering)
The present study deals with preparation of Al hybrid metal matrix composites by the stir casting technique. In this work, Al5052 alloy was selected as the main metal which reinforces with zirconium dioxide and aluminium oxide. The wear test has been conducted on the POD apparatus. 9 specimens are produced by varying reinforcements’ percentage for conduction of tests. The amount of ZrO2 reinforcement is fixed to 8wt%, while the concentration of Al2O3 varied from 5wt% to 10wt%. The parametric optimization of wear behaviour is done through the Taguchi method with L9 orthogonal array. Minitab statistical software helped to find SN ratio and ANOVA reading for each parameter: load (N), sliding speed (rpm), and wt% of reinforcements. From the ANOVA outcome, the load parameter is the highest influencing element that improves wear resistance of made samples around 46%, followed by weight% of reinforcement 29% and sliding speed 26% as second and third influenced parameters, respectively.